2015
DOI: 10.2146/ajhp140106
|View full text |Cite
|
Sign up to set email alerts
|

Effect of computerized prescriber order entry on pharmacy: Experience of one health system

Abstract: Several months after CPOE implementation, pharmacists indicated that several aspects of their workload had improved, including the process of medication order clarification, their ability to prioritize work, and their ability to move around within the hospital to respond to demand. However, pharmacists also noted that order ambiguity still existed and that the system needed to be optimized to gain efficiencies and increase clarity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 21 publications
1
21
1
1
Order By: Relevance
“…Several of the new or changed tasks associated with EMMS introduction described by pharmacists in this study are consistent with those reported in previous research . The requirement to be more vigilant to ensure that all components of a medication order are correct and the requirement to train doctors on how to use the EMMS were both new tasks reported in a US study .…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Several of the new or changed tasks associated with EMMS introduction described by pharmacists in this study are consistent with those reported in previous research . The requirement to be more vigilant to ensure that all components of a medication order are correct and the requirement to train doctors on how to use the EMMS were both new tasks reported in a US study .…”
Section: Discussionsupporting
confidence: 86%
“…The consequences were reported to be duplicated data entry, navigating across multiple systems, more paperwork for outpatient pharmacists and not enough computers to perform their work. Some of the benefits reported in other studies, such as faster verification, also appear to have not been achieved as a result of the workflow misalignment. Reorganisation of work was perceived by pharmacists to be a negative thing.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Previous studies have shown that while implementing CPOE can improve the safety and efficiency of order processing, it can create new challenges and resource demands that place increased burden on pharmacists, such as increasing new types of errors and problems caused by CPOE systems. [26][27][28][29] While CPOE systems can increase efficiency in many areas, such systems should be monitored by management so any new problems that arise can be addressed.…”
Section: A Particular Facet Of the Results Is That While Time Spent Onmentioning
confidence: 99%
“…Indeed, nurses' views on CPOE implementation are different to those of physicians [11] [12]. Conversely, pharmacists seem more satisfied with CPOE implementation [29] than physicians [30].…”
Section: Cpoe Was Never Perceived As Superior To Pboe Qualitative Anmentioning
confidence: 99%